Strategi Sosialisasi Program Jaminan Kesehatan Nasional (JKN) Badan Penyelenggaraan Jaminan Sosial (BPJS) Kesehatan Bengkulu Di Kelurahan Malabero - Hetty Kurniawaty; Meiselina Irmayanti; Rasiana Saragih (Universitas Multimedia Nusantara, 2017)
This study aims to find out the socialization strategy of JKN BPJS (state run healthcare security agency) Bengkulu in Malabero. Using qualitative research approach, the data were collected from in-depth interviews. The results shows that BPJS Health Bengkulu has done some steps of socialization strategy. It includes determining the focus of socialization, paying attention to segmentation of target audience, formation method, and selection of socialization channel. Direct socialization has been seen in the implementation of seminars, discussions, group communication, and services carried out by BPJS Health officials. In addition to seminars, discussions, presentations and two-way communication were also seen at both the BPJS Health office and at the BPJS Center in the hospital, communication via satellite and so on. There is also indirect socialization conducted by using mass media, such as advertisement in Bengkulu People's newspaper, Bengkulu Express newspaper, RRI radio, PRO 2 FM radio, TV Bengkulu, ESA TV, and BE TV. They also spread the information through media banners, posters, pamphlets, leaflets, and banners. Key Words: Strategy, socialization, BPJS, target audience, media, social security system